2022
DOI: 10.15252/embj.2022111304
|View full text |Cite
|
Sign up to set email alerts
|

Circadian time‐ and sleep‐dependent modulation of cortical parvalbumin‐positive inhibitory neurons

Abstract: Parvalbumin‐positive neurons (PVs) are the main class of inhibitory neurons in the mammalian central nervous system. By examining diurnal changes in synaptic and neuronal activity of PVs in the supragranular layer of the mouse primary visual cortex (V1), we found that both PV input and output are modulated in a time‐ and sleep‐dependent manner throughout the 24‐h day. We first show that PV‐evoked inhibition is stronger by the end of the light cycle (ZT12) relative to the end of the dark cycle (ZT0), which is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 78 publications
1
2
1
Order By: Relevance
“…Previous studies have found that diurnal variation in the frequency of excitatory and inhibitory transmission occurs in opposing phases in PV and pyramidal cells in the cortex (Bridi et al, 2020;Zong et al, 2023). However, in this study, we find that there is no diurnal change in the excitatory drive to PV cells.…”
Section: Discussioncontrasting
confidence: 87%
“…Previous studies have found that diurnal variation in the frequency of excitatory and inhibitory transmission occurs in opposing phases in PV and pyramidal cells in the cortex (Bridi et al, 2020;Zong et al, 2023). However, in this study, we find that there is no diurnal change in the excitatory drive to PV cells.…”
Section: Discussioncontrasting
confidence: 87%
“…42 Parvalbumin-positive neurons, the main class of inhibitory neurons in the mammalian CNS, in the supragranular layer of the mouse primary visual cortex (V1), evoke stronger inhibition in anticipation of awake. 43 Similar findings were found in healthy human subjects using transcranial magnetic stimulation: GABA-mediated intracortical inhibition is highest in the morning and progressively decreases during the day. 44 There is limited data on how well neurons from different brain regions can generate and sustain own independent rhythms without input from the SCN: although this has been shown for neurons from the retina and the olfactory bulb, 35,45 neurons from the medial habenular nucleus, an efferent target of the SCN, are not able to sustain rhythms in vitro.…”
Section: Neuronal Clockssupporting
confidence: 72%
“…Given the direct coupling of the changes in [Cl - ] i to the biochemical state of neurons, and the well-established role of synaptic inhibition in shaping all manner of neuronal activity 73 79 , we suggest that the changes we describe here, could constitute an important determinant of the distinct neuronal activity patterns, contributing to the cycle of brain states through the day. There are, of course, other neuronal daily fluctuations, including changes in firing rates 7 9 , 80 , in the number, strength and structure of synapses 10 13 , metabolic state 16 , gene expression and protein phosphorylation 17 , 18 ; the relative importance of these different factors, and the degree to which they are coordinated, or might offset each other, will be an important topic of future research.…”
Section: Discussionmentioning
confidence: 99%